2012
DOI: 10.1590/s1413-81232012001100022
|View full text |Cite
|
Sign up to set email alerts
|

Acesso à assistência odontológica no acompanhamento pré-natal

Abstract: This study sought to evaluate the self-perceived response to dental care during prenatal assistance in the Unified Health System (SUS) in the Metropolitan Region of Vitória, Espírito Santo, Brazil. 1032 postpartum women were interviewed and 1006 prenatal records copied. Postpartum women's self-perceived response was measured by the Oral Health Index Profile-14. When an impact was identified, dental care rendered in educational, preventive and curative terms was considered adequate. When there was no impact, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
37

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 25 publications
0
4
0
37
Order By: Relevance
“…In the Family Health Strategy (FHS), health professionals play an important role in the development of prenatal service care , providing specific guidance and advice for pregnancy and childbirth for the woman and her companion. However, multiprofessionality does not guarantee interdisciplinarity or project integration in the community [14][15][16][17] . Moura et al 18 found that in several municipalities of the State of Piaui the doctor and the dentist are not devoted enough in planning meetings, which may impair teamwork.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Family Health Strategy (FHS), health professionals play an important role in the development of prenatal service care , providing specific guidance and advice for pregnancy and childbirth for the woman and her companion. However, multiprofessionality does not guarantee interdisciplinarity or project integration in the community [14][15][16][17] . Moura et al 18 found that in several municipalities of the State of Piaui the doctor and the dentist are not devoted enough in planning meetings, which may impair teamwork.…”
Section: Discussionmentioning
confidence: 99%
“…This is not the same reality reported by pregnant women enrolled in the HFS at the city of Picos, State of Piaui, since among the few who sought care during pregnancy, very few reported attendance obstacles. Along with this, the low balance between seeking for public and private service, points to issues that may hamper the admittance of pregnant women to dental care in the FHS, such as the difficulty in scheduling appointments and service refusal to the pregnant patient by the surgeon dentist 17 . Similar to literature, pain was the main reason reported by those pregnant women attending the service due to periodontal disease, although the majority reported not receiving dental guidelines on how to avoid oral health problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No entanto, neste estudo não foi evidenciado registro de consultas odontológicas por gestantes no período estudado. Estudo brasileiro demonstra que apenas 17% das gestantes receberam algum tipo de assistência odontológica (18) , evidenciando que esta não é uma realidade apenas local.…”
Section: Discussionunclassified
“…A literatura tem demonstrado que existe uma lacuna na formação de cirurgiões-dentistas que proporciona desconhecimento ou medo quanto à abordagem a esse público, levando a postergação de procedimentos ou não intervenção de maneira resolutiva (SANTOS NETO et al, 2012). Atualmente, os cursos de odontologia têm sofrido mudanças em suas grades curriculares que visam acentuar os cuidados na atenção primária e a formação mais humanística, generalista, crítica e reflexiva dos cirurgiões-dentistas (SILVEIRA; GARCIA, 2015).…”
Section: Introductionunclassified